Pluralisme Internal Islam: Model Koeksistensi Nahdlatul Ulama dan Muhammadiyah dalam Bingkai Pancasila - Sabil Syuhada; Muhammad Nobel Maulana; Adilla Fauziah Aliva; Niki Salwanabila; Srihana Marhadi (Reflection : Islamic Education Journal, 2025)
Indonesia’s rich religious, ethnic, and cultural diversity has long been accompanied by challenges related to socio-religious conflict. One important yet often overlooked dimension is intra-religious tension, illustrated by the differing perspectives of Nahdlatul Ulama (NU) and Muhammadiyah—the two largest Islamic organizations in the country. This study examines how these organizations manage their doctrinal differences (khilafiyah) and uphold tolerance as an expression of the First Principle of Pancasila. Using a qualitative literature review, the research analyzes organizational documents, scholarly works, and academic articles concerning both groups. Findings show that their divergence stems primarily from distinct methodological frameworks. NU follows the Aswaja tradition, accommodating local culture through the concept of Islam Nusantara, adhering to classical jurisprudential schools, and applying the maxim al-muhafadzah. In contrast, Muhammadiyah employs the Manhaj Tarjih and a Tajdid (renewal) approach centered on purification and modernization, forming the basis of its Progressive Islam vision. Despite differences in jurisprudential practice, both organizations share a commitment to moderation (wasathiyyah). NU expresses tolerance through its principles of Tawassuth, Tawazun, Tasamuh, and the Trilogy of Brotherhood, whereas Muhammadiyah emphasizes justice and respect for diversity in its Guidelines for Islamic Life. Their mutual acceptance of Pancasila—as Darul Ahdi wa Syahadah for Muhammadiyah and the foundation of Ukhuwah Wathaniyah for NU—demonstrates that internal Islamic pluralism can strengthen, rather than weaken, national unity.